Waking the Sleeping Giant: Agricultural intensification, extensification or stagnation in Mali's Guinea Savannah. (October 2016) - Ollenburger, Mary H.; Descheemaeker, Katrien; Crane, Todd A.; Sanogo, Ousmane M.; Giller, Ken E.
Abstract: The World Bank argued that West Africa's Guinea Savannah zone forms part of "Africa's Sleeping Giant, " where increases in agricultural production could be an engine of economic growth, through expansion of cultivated land in sparsely populated areas. The district of Bougouni, in southern Mali, falls within this zone. We used multiple data sources including a panel survey, remote sensing-based land cover classification, population data, and farmer focus group discussions, to investigate whether the area is following a commonly-described pathway of agricultural intensification due to increasing land scarcity. We then used our understanding of historical change to explore plausible future pathways. Bougouni forms part of the expansion zone of the CMDT, which since the mid-1980s has provided support for intensive agricultural systems of cotton-maize rotations with animal traction and use of mineral fertilizer. In the period of the panel survey (1994–2012), cropped land at household level was correlated with household size: households with less than one full team of draft oxen cultivated 0.50 ha/family member, while households with two or more teams cultivated 0.82 ha/family member ( R 2 > 0.8). At the village level, cropped land increases varied with the amount of remaining available land and the importance of off-farm income. We see some intensification in maize and cotton, and corresponding improvements in food self-sufficiency. However, despite increasing fertilizer use, average maize and cotton yields remain around 1600 and 900 kg/ha respectively, well below national averages. Other crops are still grown in outfields relying on long fallows with limited nutrient inputs. Thus rather than either intensification or extensification the agricultural situation may be best described as stagnation. This may be due to limited incentives to invest in agriculture when compared to opportunities such as gold mining or small businesses, which (in 2012) contribute at least 25% of household income to ten out of 29 households. In future, cropland expansion will likely continue, which could lead to increased conflict between farmers and transhumant herders, and could lead to increased inequality at village level. Factors mitigating the tendency to land expansion include opportunities for off-farm income and migration, or market opportunities and capacity to produce high-value crops such as mango, cashew, or vegetables. This could preserve some remaining savannah area for grazing use and conservation purposes. Understanding household livelihood systems as part of a network of complex social and ecological factors allows the identification and exploration of multiple viable pathways towards desirable futures. Highlights: Qualitative and quantitative data was used to explore pathways of change since 1980. Cropped area was strongly correlated to household size and number of draft teams. As area per person was constant, cropped area expanded as village populations grew. Limited intensification occurred in maize since 2004, other crop yields stagnated. Farmer incentives need to change if future growth in agriculture is to occur.